Socio-demographic profile of organic food consumers in Republika Srpska - Jovana Galić (Anali Ekonomskog fakulteta u Subotici, 2022)
The aim of this research is to determine the profile of organic food consumer in Republika Srpska according to its socio-demographic characteristics and to analyse if there is significant relation between consumer education level and intention to purchase organic food. For this purpose questionare survey was conducted on random representative sample. Consumers are segmentated according to their purchase habits and profile was done for each segment. Results show that there are socio-demographic characteristics that determine different profiles and that education level has positive and significant relation to intention to purchase organic food.